Cooperation among unrelated ant queens provides persistent growth and survival benefits during colony ontogeny - Madeleine M. Ostwald (Nature Portfolio, 2021)
Abstract The fitness consequences of cooperation can vary across an organism’s lifespan. For non-kin groups, especially, social advantages must balance intrinsic costs of cooperating with non-relatives. In this study, we asked how challenging life history stages can promote stable, long-term alliances among unrelated ant queens. We reared single- and multi-queen colonies of the primary polygynous harvester ant, Pogonomyrmex californicus, from founding through the first ten months of colony growth, when groups face high mortality risks. We found that colonies founded by multiple, unrelated queens experienced significant survival and growth advantages that outlasted the colony founding period. Multi-queen colonies experienced lower mortality than single-queen colonies, and queens in groups experienced lower mortality than solitary queens. Further, multi-queen colonies produced workers at a faster rate than did single-queen colonies, even while experiencing lower per-queen worker production costs. Additionally, we characterized ontogenetic changes in the organization of labor, and observed increasing and decreasing task performance diversity by workers and queens, respectively, as colonies grew. This dynamic task allocation likely reflects a response to the changing role of queens as they are increasingly able to delegate risky and costly tasks to an expanding workforce. Faster worker production in multi-queen colonies may beneficially accelerate this behavioral transition from a vulnerable parent–offspring group to a stable, growing colony. These combined benefits of cooperation may facilitate the retention of multiple unrelated queens in mature colonies despite direct fitness costs, providing insight into the evolutionary drivers of stable associations between unrelated individuals.